1999
DOI: 10.1038/sj.sc.3100767
|View full text |Cite
|
Sign up to set email alerts
|

Screening cystoscopy in chronically catheterized spinal cord injury patients

Abstract: Study design: Retrospective review. Objectives: An annual screening cystoscopy protocol was begun at our institution in an attempt to minimize the morbidity and mortality of bladder cancer in the chronically catheterized spinal cord injured (SCI) population. The objectives of this study are: (1) to present the results of 6 years of screening for primary bladder cancer in this population, and (2) examine the suitability of this protocol based upon accepted principles of cancer screening. Setting: Veterans hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…36 Inherent in the treatment of neurogenic bladder dysfunction consisting of indwelling catheters is the necessity for life-long surveillance cystoscopy, urinary cytology 37 and upper tract imaging. Authors have previously described various schedules for surveillance cystoscopy, ranging from annual examination, to every 3 months in those with a history of bladder stones, 38 or those with significant squamous metaplasia. 39,40 A recent retrospective analysis by Hamid 41 which examined the role of surveillance cystoscopy and biopsy did not demonstrate evidence to support more than annual cystoscopic examination, with the biopsy only of suspicious lesions.…”
Section: Risk Of Bladder Neoplasiamentioning
confidence: 99%
“…36 Inherent in the treatment of neurogenic bladder dysfunction consisting of indwelling catheters is the necessity for life-long surveillance cystoscopy, urinary cytology 37 and upper tract imaging. Authors have previously described various schedules for surveillance cystoscopy, ranging from annual examination, to every 3 months in those with a history of bladder stones, 38 or those with significant squamous metaplasia. 39,40 A recent retrospective analysis by Hamid 41 which examined the role of surveillance cystoscopy and biopsy did not demonstrate evidence to support more than annual cystoscopic examination, with the biopsy only of suspicious lesions.…”
Section: Risk Of Bladder Neoplasiamentioning
confidence: 99%
“…A urological screening program was carried out in 500 SCI patients; cystoscopy was carried out in those who used some form of urinary catheter for at least 5 or 10 years (depending on smoking status). 35 No cancers were detected with the screening protocol. Three patients from this cohort were diagnosed with bladder cancer outside of the screening protocol; two of these patients did not meet the criteria for yearly cystoscopy, as they used external urine collection devices, and the remaining patient had a normal cystoscopy and biopsy 4 months before their diagnosis as part of the screening protocol.…”
Section: Risk Factors For Development Of Bladder Cancer In Sci Patientsmentioning
confidence: 99%
“…Several studies demonstrated that screening cystoscopy alone is not sufficiently sensitive and specific to be used as a surveillance tool in SCI patients. Yang and Clowers did not detect a single tumor in 59 patients undergoing a total of 156 cystoscopies, the majority of which had to be performed under general anesthesia, 12 as especially patients with an SCI above the level of Th10 are at risk for autonomic dysreflexia, a potentially life-threatening complication. 13 Particularly in patients with indwelling catheters, bladder tumor detection merely based on the endoscopic appearance is virtually impossible, as it is not possible to reliably distinguish the morphologic alterations caused by the catheters from bladder tumors.…”
Section: Discussionmentioning
confidence: 98%